Dental service utilization among junior secondary school students in Ibadan, Nigeria (2010)
The study was carried out to determine factors affecting oral health care service utilization among a representative sample of junior secondary school children in Ibadan, Nigeria. The study was a cross sectional one in which self administered questionnaire was filled by each student. Data were collected on their socio-demographic characteristics, previous visit(s) to the dental clinic and reasons for the visit(s), reasons for non dental visits for those who have never visited the dentist, the students’ beliefs in regular dental visits and reasons for these beliefs. Only 457 students completed their questionnaires reasonably well and their responses were analysed. Their mean age was 13.04 1.10 years. Over 80% of the children claimed they have never visited the dentist and lack of perceived need accounted for 82.8% of the various reasons given for the non visit. Sixty eight point nine percent of the children believed in regular dental visits while 27.8% of them did not believe in regular dental visits. Equity in access and opportunity for disease prevention among young adolescents may be achieved by school oral health program whereby regular oral health talks/education is instituted.